Two different conformational states of the KirBac3.1 potassium channel revealed by electron crystallography. - Kuo, A; Domene, C; Johnson, L; Doyle, D; Vénien-Bryan, C (2005)
Potassium channels allow the selective flow of K(+) ions across membranes. In response to external gating signals, the potassium channel can move reversibly through a series of structural conformations from a closed to an open state. 2D crystals of the inwardly rectifying K(+) channel KirBac3.1 from Magnetospirillum magnetotacticum have been captured in two distinct conformations, providing "snap shots" of the gating process. Analysis by electron cryomicroscopy of these KirBac3.1 crystals has resulted in reconstructed images in projection at 9 A resolution. Kir channels are tetramers of four subunits arranged as dimers of dimers. Each subunit has two transmembrane helices (inner and outer). In one crystal form, the pore is blocked; in the other crystal form, the pore appears open. Modeling based on the KirBac1.1 (closed) crystal structure shows that opening of the ion conduction pathway could be achieved by bending of the inner helices and significant movements of the outer helices.